Location dynamics of business services in the urban landscape of Copenhagen: Imaginary spaces of location - Lars Winther (Belgeo)
The paper examines the current transformation and spatial restructuring of the urban economy with focus on the location dynamics of business services, especially during the past decade of economic growth. Since the early 1990s, Copenhagen has experienced economic growth and job creation created mainly by the service industries, including the rise of knowledge intensive business services. The location dynamics of the 1990s growth were more ambiguous than the patterns of the 1980s. The location in the 1990s involved both a concentration in the central part of the urban landscape, an extension of existing locations in suburbia and growth in new locations in the urban landscape. The paper provides empirical evidence of the new complexity of location dynamics and introduces imaginary spaces of location to explain the diversity of location. Imaginary spaces of location are social construction of firms based on the perception, experience and interpretation of the firm’s location.